2020
DOI: 10.3389/fpls.2020.590889
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Smartphone-Based Object Detection Model, PlantVillage Nuru, in Identifying the Foliar Symptoms of the Viral Diseases of Cassava–CMD and CBSD

Abstract: Nuru is a deep learning object detection model for diagnosing plant diseases and pests developed as a public good by PlantVillage (Penn State University), FAO, IITA, CIMMYT, and others. It provides a simple, inexpensive and robust means of conducting in-field diagnosis without requiring an internet connection. Diagnostic tools that do not require the internet are critical for rural settings, especially in Africa where internet penetration is very low. An investigation was conducted in East Africa to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Identifies disease and classifies the image under the specified category with the accuracy score of 93%. A deep learning based object detection model namely Nuru 28 is developed to diagnose the symptoms of the cassava plant diseases with great accuracy and the performance is compared with the experts, agricultural officers and farmers. The novel deep learning based method is proposed in which it integrates the deep residual convolutional neural network and distinct block processing 29 for classifying the cassava mosaic disease and it is analyzed with plain convolutional neural network by using various performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Identifies disease and classifies the image under the specified category with the accuracy score of 93%. A deep learning based object detection model namely Nuru 28 is developed to diagnose the symptoms of the cassava plant diseases with great accuracy and the performance is compared with the experts, agricultural officers and farmers. The novel deep learning based method is proposed in which it integrates the deep residual convolutional neural network and distinct block processing 29 for classifying the cassava mosaic disease and it is analyzed with plain convolutional neural network by using various performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Conditions such as the quality and quantity of images used to train the model and the variation and complexity of the disease symptoms can influence the accuracy (sensitivity and specificity) of the diagnostic system [47]. In-field conditions, such as sunlight, wind and rain, can also affect the accuracy of the diagnosis system.…”
Section: Detection Of the Disease Using Smartphone Image Analysismentioning
confidence: 99%
“…In-field conditions, such as sunlight, wind and rain, can also affect the accuracy of the diagnosis system. Mrisho et al [47] and Ramcharan et al [45] showed that the in-field accuracy of PlantVillage Nuru using one leaf (21-59%) was lower than the on-screen accuracy (43-81%). When the number of leaves inspected by PlantVillage Nuru was increased to six per plant, however, accuracy increased to 93% for cassava mosaic disease, 73% for cassava brown streak disease and 93% for cassava green mite [47].…”
Section: Detection Of the Disease Using Smartphone Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the classification was based on Artificial Neural Networks (ANNs). In a recent study, researchers reported the performance of a deep learning object detection model for diagnosing plant diseases and pests [30]. The model was trained on 2756 images of cassava leaves exhibiting pest and disease symptoms.…”
Section: Introductionmentioning
confidence: 99%